A Lyapunov-Based Dual Controller Approach With PSO Tuning for Steer-by-Wire Systems With Artificial Steering Feel - Able Alex; Abdul Saleem (IEEE Access)
The automotive industry has seen a significant transformation in steering control systems with the introduction of steer-by-wire technology, breaking the traditional coupling between the road wheel and steering wheel. This decoupling necessitates precise synchronization between steering inputs and road wheel movements, along with effective steering feedback responses to ensure intuitive driver control. This study addresses these challenges by integrating artificial steering sensation through a strategic Lyapunov-based dual controller, enhancing the efficiency of both the steering wheel angle and road wheel angle control loops. Controller gains are optimized systematically using particle swarm optimization, and the effectiveness of the proposed approach is validated across diverse driving scenarios using the MATLAB/Simulink platform. Results demonstrate that the Lyapunov-based dual controller significantly reduces tracking errors and outperforms a typical sliding mode controller under various road conditions.